FENOMENA CHILDFREE DALAM PERNIKAHAN PERSPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG NO.1 TAHUN 1974 TENTANG PERKAWINAN - Raja Rahmat Rayhan; Abdullah Afif (JURNAL ILMIAH NUSANTARA, 2024)
Based on the phenomenon of childfree in marriage which is common, this sparked controversy especially in Indonesia, because it is not in line with the cultural customs and beliefs that exist, then how the view of Islamic law using the theory of marriage murals and views of the marriage law no. 1 of 1974 against the legal status of childless such. This research is normative qualitative research using the study of documents or libraries using normative approaches. The conclusion of this study is generally that, the phenomenon of childfree in marriage is a controversial thing because it does not conform to one of the purposes of marriage in Islam, it is reinforced by the theory of Mursalah that says that childfree goes behind with three categories of Mushah, namely: dharuriah, Hajiyah and Tahsiniah, but different from the view of the marriage law which, the purpose of marriages according to the law No. 1 of 1974 is to form a happy and eternal family, which prioritizes that having a child is the right of each person, because there are two different perspectives of both such prospects that can be set as arguments.